Artritis reumatoide y riesgo cardiovascular - Karsulovic C., Claudio; Guerrero P. , Julia; Goecke S., Annelise (Revista Hospital Clínico Universidad de Chile, 2019)
Cardiovascular disease (CVD) is the most frequent cause of premature death according to data from the American Heart Association and World Health Organization. Incidence and prevalence are on the rise. Rheumatoid Arthritis (RA) is the most common autoimmune disease. It is a chronic and systemic disease characterized by articular involvement with deformity ranging from persistent pain to premature disability. CVD is the most frequent cause of death in RA patients, even more than in diabetes mellitus 2 or chronic kidney disease. Multiple CVD risk scales have been tested in order to obtain a more accurate prediction of premature death by stroke or myocardial infarction in RA patients. Most of the scales, even those adjusted including RA features like inflammation and antibodies titles, have failed to properly predict the real CVD risk. Individually, RA specific autoantibodies have been related with increased CVD risk and multiple mechanistic explanations have arisen, generating even a new concept called “Autoimmune Atheromatosis”. Nevertheless, this association fails to give a full understanding of the accelerated and aggressive atheromatosis process that RA patients develop. New studies oriented to mechanistic explanations are necessary in order to develop new diagnostic targets and prevention strategies.